Characteristics of smes operated by malay entrepreneurs / Salina Daud and Abdul Ghafar Hussin - Daud, Salina; Hussin, Abdul Ghafar (2004)
Entrepreneurship development among small and medium-sized enterprises (SMEs) operators is an important component in Malaysian government agenda nowadays. Nevertheless, designing appropriate course of actions for their development is difficult given the lack of pertinent information on the entrepreneurs and the businesses that they venture into. To close some of the research gaps, this study examined the characteristics of SMEs that are operated by Malay entrepreneurs in the state of Pahang. Among the characteristics that were examined include their main business activity, and whether they were involved in more than one business, the types of firm's ownership, their age when they started the business, their education level, their sources of initial capital, the location of their business operations and whether the businesses were operated by a single owner or an entrepreneurial team. The data were gathered through analyzing the statistical data collected from 408 members of Malay Chamber of Commerce (DPMM), Pahang and interviews with 32 entrepreneurs from various sectors. The study found that 27 percent of the entrepreneurs were involved in retailing businesses, followed by contractor businesses 21 percent. The type of main business activity operated varied with district. 49 percent of the entrepreneurs are concentrating on one business activity. 74 percent of the SMEs were registered as sole proprietorship and were operated by entrepreneurial team managers. All respondents have formal education, with 44 percent having STPM/Diploma qualification. Findings from this study can serve as a basis for comparison for researchers who may examine business characteristics of SMEs owned by non-Malay groups in the state of Pahang or any other states in the future.